The effect of plyometric training on improving the explosive strength of volleyball players aged under U19 - SAMAR, Mohamed; HIMOUD, Ahmed (Journal of Human Sciences, 2020)
The study aimed to identify the effect of plyometric training program in improving volleyball players, explosive strength, because of the nature of the study we selected the experimental approach, and physical tests for explosive strength were used as a tool to collect data. The sample of this research concerns volleyball players aged less than 19 of the younger generation team of Ouled Oudwan Municipality who belong to the excellent department; 16 players have been chosen to participate in the test and theywere divided into 08 players in each group. The plyometric training was applied on the experimental group for 8 weeks, while the traditional program was applied on the control group. The results of this study show thatthe plyometric exercises has a positive effect on improving the trait of explosive strength in volleyball sport players aged less than 19 years, also the findings show that there are statistically significant differences between the pre and post measurement in the experimental sample in all tests in favor of the post-test, and there are no statistically significant differences between the experimental sample and the control in the post- measurements.